P-488 Perceptions of gamete and embryo donation recipient parents about the online experimental and control programs in the TELL Tool feasibility clinical trial at immediate post-test. (30th June 2022) - Hershberger, P; Gallo, A M; Gruss, V; Steffen, A D; Adlam, K; Driessnack, M; Grotevant, H D; Klock, S C; Pasch, L
Abstract: Study question: What are parents' initial perceptions about the online experimental and control programs at immediate post-test? Summary answer: Parents reported overall acceptability of the online instructions, technological navigation, length, and quality of videos, as well as suggestions for further improvement. What is known already: Multiple investigations have examined the reasons why parents who used donated gametes or embryos, decide to inform their children that they were conceived through third-party reproduction. A consistent theme in this research is parental calls for strategies and tools to aid parents with disclosure to their children. Despite these calls from parents, little research has focused on developing new methods of delivering parent-focused materials that aim to assist parents in their disclosure process. To address this concern, we developed an online experimental program called the T ool to E mpower Parental TeL ling and TaL king (TELL Tool) and completed alpha testing. Study design, size, duration: A 3-month feasibility clinical trial. Participants/materials, setting, methods: Donor sperm, egg, and embryo recipient parents were randomized to either an experimental TELL Tool program or a control program focused on good parenting practices. Both the TELL Tool and the control programs are administered online. To date 13 parents have completed the experimental or control program and each participant has answered an immediate post-test survey about the acceptability of the program. Descriptive statistics and qualitative content analysis guided the analysis. Main results and the role of chance: The sample consists of 13 U.S. parents between 35 to 53 years ( M = 41.3 years). The parents used donated sperm ( n = 5), eggs ( n = 2), sperm and eggs ( n = 2) or embryos ( n = 4) and their children were between 1 to 12 years ( M = 5.7 years). Most parents were female ( n = 11) and White ( n = 10). Parents were asked to rate the level of truthfulness about the acceptability of the online programs (ratings: 1 to 5, with 1 being "not at all true" to 5 being "very true"). Responses about the: (1) instructions provided for accessing the program were easy, were: range 3 to 5, M = 3.9; (2) technological navigation within the program was problematic, were: range 1 to 5, M = 2.7; (3) length of the program was too long, were: range 1 to 5, M = 3; and (4) videos within the program were helpful, were: range 3 to 5, M = 3.69. Responses to the open-ended questions provided insights to the ratings, such as parents' statements about specific technological issues (e.g., ability to print resources, ease of navigating in-and-out of the program). Limitations, reasons for caution: Preliminary data are reported for the feasibility trial at the immediate post-test timepoint as recruitment is ongoing. As the 3-month study unfolds, additional data will be obtained to allow for more in-depth understanding of parents' perceptions about the acceptability of the experimental TELL Tool and control programs. Wider implications of the findings: The acceptability of the online research for donor gamete and embryo recipient parents may illuminate access issues to these often hidden and dispersed parents and their families across the lifespan. Parents' responses can provide a window of understanding for other decision aids that target health promotion among parents and children. Trial registration number: NCT04841967